Management of COVID-19 in Children and Adolescents -A Practical Up-to Date Guideline - Al-Momen, Hayder; Al-Tamimi, Wisam Younis; Hussein, Hussein khudhair; Raham, Tareef Fadhil (AL-Kindy College Medical Journal, 2020)
Sufficient high-quality data are unavailable to describe the management approach and guideline of COVID-19 disease in pediatric and adolescent population which may be due to mild presentation in most of cases and less severe complications than older ages. World Health Organization was concerned with the establishment of an approved guideline to manage the increasing number of COVID-19 patients worldwide aiming to prevent or lessen COVID-19 global burden. The clinical features have a wide spectrum starting from uncomplicated mild illness, mild-moderate pneumonia, severe pneumonia, acute respiratory distress syndrome, sepsis, septic shock, and multisystem inflammatory syndrome in children. Many important definitions were developed to identify the COVID-19 case status including confirmed, suspected, and probable case. Many laboratory tests may be beneficially done but reverse transcriptase – polymerase chain reaction (RT-PCR) for SARS-CoV-2 RNA is diagnostic. Patient isolation and adequate intake of fluid and calories, antipyretics (preferably paracetamol), antibiotics (in secondary bacterial infections), and bed rest are the mainstay of approved supportive treatment. While oxygen supplementation may be added in moderate to severe cases; anticoagulation prophylaxis (enoxaparin) is strongly advised in children with certain situations where hypercoagulability state is identified, and therapy should be evaluated based on risk factors. New approaches, drugs, and therapies are currently under research to manage COVID-19 pediatric and adolescent patients including antivirals (lopinavir/ritonavir, and favipiravir), remdesivir, tocilizumab, dexamethasone, convalescent plasma, and specific treatment of multisystem inflammatory syndrome in children (immunoglobulin, steroids, tocilizumab, anakinra, and aspirin). The practical approach was summarized in a flow chart scheme to assist health care professionals to manage COVID-19 in children and adolescents within a rapid look though details are given in the text.